Case Report of Novel Genetic Variant in KCNT1 Channel and Pharmacological Treatment With Quinidine. Precision Medicine in Refractory Epilepsy - Kravetz, M. C.; Viola, M. S.; Prenz, J.; Curi, M.; Bramuglia, G. F.; Tenembaum, S. (Frontiers in Pharmacology, 2021)
Introduction In this work we present a female infant patient case with a severe encephalopathy of early onset epileptic syndrome. Although many pharmacological schemes were attempted, she developed an epileptic encephalopathy with poor response to antiepileptic drugs and progressive cerebral dysfunction. Aim To present the pharmacological response and therapeutic drug monitoring of a paediatric patient with a sever encephalopathy carrying a genetic variant in KCNT1 gene, whose identification led to include quinidine in the treatment regimen as an antiepileptic drug. Case report Patient showed slow rhythmic activity (theta range) over left occipital areas with temporal propagation and oculo-clonic focal seizures, without tonic spasms three months after birth. At the age of 18 months showed severe impairments of motor and intellectual function, with poor eye contact. When the patient was 4 years old, a genetic variant in the exon 24 of the KCNT1 gene was found. This led to the diagnosis of Epilepsy of Infancy with Migrating Focal Seizures or EIMFS. Due to its activity as KCNT1 blocker, quinidine was introduced as therapeutic alternative for epilepsy besides topiramate (200 mg/day) and nitrazepam (2 mg/day). Therapeutic drug monitoring (TDM) of quinidine needed to be implemented to avoid toxicity as well as electrocardiogram studies. Thus, TDM for doses adjustment was performed to establish the individual therapeutic range of the patient. Seizures were under control after quinidine levels above 1.5 mcg/mL (65-70 mg/kg q.i.d). Anyway, quinidine levels higher than 4.0 mcg/mL, were related to higher risk of suffering arrhythmia due to prolongation of QT segment. Despite initial intention to withdrawal topiramate completely, quinidine was no longer effective and failed to maintain seizures control. Due to this necessary interaction between quinidine and topiramate, topiramate was stablished in a maintenance dose of 40 mg/day. Conclusion The implementation of Precision Medicine by using tools such as next generation sequencing technology led to diagnose this patient with a severe encephalopathy of early onset epileptic syndrome. TDM was fundamental to implement a successful treatment with a potassium channel blocker with a narrow therapeutic index, such as quinidine.